The language and literature of the New Testament essays in honor of Stanley E. Porter's 60th birthday - Porter, Stanley E. 1956-; Fuller Dow, Lois K.; Evans, Craig A. 1952-; Pitts, Andrew W. (Leiden Boston Brill, 2016)
Preliminary Material -- Interdisciplinary New Testament Scholarship: An Introduction to the Research of Professor Stanley E. Porter /Andrew W. Pitts -- 1 Setting Scholarship Back a Hundred Years? Method in the Septuagint Commentary Series /Richard S. Hess -- 2 The Past, Present, and Future of the OpenText.org Annotated Greek Corpus /Christopher D. Land and Francis G. H. Pang -- 3 Computer-Aided Linguistic Analysis for a Single Manuscript Witness: Preparing to Map the OpenText.org Annotation /Catherine Smith and Matthew Brook O’Donnell -- 4 Überlegungen zur angeblichen Textverderbnis von Apg 17,27 (Codex Bezae Cantabrigiensis) und zu Joh 8,25 /Hans Förster -- 5 Restoring a Vernacular Form of the Word for “Glass” in the Text of Revelation /John A. L. Lee -- 6 Sense Units and Manuscript Families: A Test Proposal /Sean A. Adams -- 7 Christian Demographics and the Dates of Early New Testament Papyri /Craig A. Evans -- 8 The Use of Greek in First-Century Palestine: An Issue of Method in Dialogue with Scott D. Charlesworth /Hughson T. Ong -- 9 Grappling with Paul’s Language: How a Greek Might Struggle /R. Dean Anderson -- 10 Exploring Linguistic Variation in an Ancient Greek Single-Author Corpus: A Register Design Analysis of Josephus and Pauline Pseudonymity /Andrew W. Pitts and Joshua D. Tyra -- 11 Οὖν in the New Testament: The Minimal Semantic Contribution of a Discourse Marker /Cynthia Long Westfall -- 12 The Telic Conjunctions of Isaiah 6:9–10 in Mark’s Mythopoeia /Thomas R. Hatina -- 13 Greek Tenses in John’s Apocalypse: Issues in Verbal Aspect, Discourse Analysis, and Diachronic Change /Buist M. Fanning -- 14 The Gospel according to Malachi /Mark J. Boda -- 15 Σημεῖα, Signs, as a Hyperlink between the Fourth Gospel and the Greek Pentateuch /Ronald D. Peters -- 16 The Authentication of John: Self-Disclosure, Testimony, and Verification in John 21:24 /Charles E. Hill -- 17 Getting Along: Politeness Theory and the Gospels /Jonathan M. Watt -- 18 The Structure and Content of Stephen’s Speech compared to Old Testament Credos /Thomas H. Olbricht -- 19 Minding the Gap: Why Paul’s Conversion Matters for Christology /Darrell Bock -- 20 Introducing Foreign Deities: The Documentary Evidence /Eckhard J. Schnabel -- 21 The Apostle of the Heretics? /James D. G. Dunn -- 22 Habakkuk, Paul, and the End of Empire: A Fresh Perspective on Romans 13:1–7 /Nicholas Perrin -- 23 The Apostle and the Doctor: Lloyd-Jones on Romans /Stephen Westerholm -- 24 A Comparison of the Fruit of the Spirit in Galatians 5:22–23 with Ancient Thought on Ethics and Emotion /Craig S. Keener -- 25 To Incline Another’s Heart: The Role of Attitude in Reader Positioning /James D. Dvorak -- 26 “Think” and “Do” Like the Role Models: Paul’s Teaching on the Christian Life in Philippians /Jae Hyun Lee -- 27 Postcolonial Perspectives on Paul’s “Jew-Gentile Problem” /Christopher D. Stanley -- 28 A Reexamination of Paul’s Opponents in Colossians /David L. Mathewson -- 29 First Timothy 5:18 and Early Canon Consciousness: Reconsidering a Problematic Text /Michael J. Kruger -- 30 The Epistle of James and the Maccabean Martyr Tradition: An Exploration of Sacred Tradition in the New Testament /Bryan R. Dyer.
In The Language and Literature of the New Testament , a team of international scholars assembles to honour the academic career of New Testament scholar Stanley E. Porter. Over the years Porter has distinguished himself in a wide range of sub-disciplines within New Testament Studies. The contents of this book represent these diverse scholarly interests, ranging from canon and textual criticism to linguistics, other interpretive methodologies, Jesus and the Gospels, and Pauline studies
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Language, style; Bible -- Criticism, interpretation, etc; Bible -- Language, style; Bible; Festschrift; Aufsatzsammlung